Prescriber Uptake and Use of Novel Lipid‐Lowering Therapies - Jimin Hwang; Eric D. Peterson; Anand Gupta; Emily Decicco; Evelyn Sarnes; Ann Marie Navar (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The uptake of novel lipid‐lowering therapy (LLT) has been low; however, variations in clinician prescribing patterns have not been well studied. This study sought to describe early prescribing patterns of novel LLT and identify factors associated with high usage. Methods We identified prescriptions for any LLT using pharmacy transaction data (covering >80% of the United States) from January 1, 2018 to December 31, 2022, and identified patients newly initiated on PCSK9i (proprotein convertase subtilisin/kexin type 9 inhibitor) monoclonal antibodies or bempedoic acid (BA). We assessed the proportion of LLT prescribers overall and by specialty who had prescribed PCSK9i and BA, and the volume of patients prescribed. The association between use of PCSK9i and BA was assessed. Results Of 996 421 LLT prescribers, only 9.2% (N=91 166) and 2.4% (N=23 674) had prescribed PCSK9i and BA, respectively, by December 31, 2022. Usage was higher among cardiologists, but still only 62.8% and 18.2% of cardiologists had given a PCSK9i or BA prescription. The top 10% of prescribers were responsible for starting 57.3% and 51.2% of PCSK9i and BA prescriptions, respectively. Conclusions The majority of US clinicians prescribing LLT have never prescribed a PCSK9i or BA, and among those who do, most have used these therapies in only a few patients. However, there exist distinct groups of early adopters and high‐volume users with higher approval rates, slightly more years in practice, and more cardiologists. Given that prescription approval rates for both PCSK9i and BA have now increased to >80% in our analysis, increasing uptake of novel LLT will require interventions to increase use among clinicians.